2011
DOI: 10.3892/or.2011.1600
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 4 inhibits leptin-induced breast cancer cell invasion

Abstract: Abstract. Obesity is a significant risk factor for post-menopausal women to develop and die from breast cancer. Leptin, an adipokine is produced in high levels in obese individuals, and its receptor is overexpressed in breast tumors and lymph node metastases. Previously, we demonstrated that leptin stimulates breast cancer cell invasion, which is correlated with breast cancer metastasis. Programmed cell death 4 (PDCD4) has been shown to block cancer cell invasion. However, whether PDCD4 blocks leptin-induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The invasiveness of HeyA8-MDR and OVCAR-5 cells treated with ZA was determined as previously described (15). Briefly, HeyA8-MDR and OVCAR-5 cells were collected and washed with serum-free media.…”
Section: Methodsmentioning
confidence: 99%
“…The invasiveness of HeyA8-MDR and OVCAR-5 cells treated with ZA was determined as previously described (15). Briefly, HeyA8-MDR and OVCAR-5 cells were collected and washed with serum-free media.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond inhibiting tumor promotion, over-expression of PDCD4 cDNA also suppresses tumor invasion or intravasation in many types of cancer cells including breast, colon, liver, gastric, and ovarian cancer (Gonzalez-Villasana et al 2012, Leupold et al 2007, Nieves-Alicea et al 2009, Wei et al 2012, Yang et al 2006, Yu et al 2014, Zhang et al 2009). On the other hand, lowering Pdcd4 expression by PDCD4 siRNA or shRNA stimulates invasion in breast, colon, lung, and nasopharyngeal cancer cells (Santhanam et al 2010, Wang et al 2008, Wang et al 2010, Yang et al 2015, Zhen et al 2017).…”
Section: Pdcd4 Inhibits Tumor Invasion and Metastasismentioning
confidence: 99%
“…While down-regulation of Pdcd4 by delivery of PDCD4 shRNA into the lung of A/J mice enhances CDK4 expression (Hwang et al 2010), indicating that Pdcd4 inhibits cell proliferation and induces apoptosis in mouse lung. In addition, it has shown that Pdcd4 inhibits invasion in breast cancer cells by enhancing the expression of tissue inhibitor of metalloproteinase 2 (TIMP2) (Gonzalez-Villasana et al 2012, Nieves-Alicea et al 2009). The TIMP2 is a natural inhibitor of the matrix metalloproteinases (MMPs), which suppresses cell migration and invasion by preventing penetration of extracellular matrix.…”
Section: Mechanisms Of Regulating Tumorigenesis By Pdcd4mentioning
confidence: 99%
“…Recent findings indicate that PDCD4 can function as a protein translation suppressor though both eIF4A-dependent or -independent pathways (Yang et al, 2003 ; Yang et al, 2004 ; Singh et al, 2011 ; Wedeken et al, 2011 ). PDCD4 is widely recognized as an important tumor suppressor, as its expression is dramatically downregulated in many cancer types, including CRC (Yang et al, 2006 ), lung cancer (Chen et al, 2003 ), breast cancer (Gonzalez-Villasana et al, 2012 ) and gastric cancer (Guo et al, 2013 ). Several studies have validated that loss of PDCD4 during tumorigenesis promotes cancer cell proliferation (Li et al, 2014 ), metastasis (Yang et al, 2006 ) and inhibits apoptosis (Wang et al, 2010b ).…”
Section: Introductionmentioning
confidence: 99%